Implementation of Digital Transformation of Voter Data Updating Management Using the Cianjur Regency KPU's Voter Data Information System Application (Sidalih) - Ali Firdaus Abdul Kadir; Benawa -; Ety Yuliati; Maryani -; Nursyamsi -; Rida Effendi (Diversity: Jurnal Ilmiah Pascasarjana, 2022)
Updating voter data is a necessity that must be carried out by the KPU so that later all Indonesian citizens can vote in the General Election to elect members of the DPR, DPD, Provincial DPRD, Regency/City DPRD, President and Vice President, and Elections to elect the Governor and Deputy Governor. , Regent and Deputy Regent and Mayor and Deputy Mayor. This study tries to examine the Voter Data Information System (Sidalih) which is owned by the General Election Commission (KPU). The goal is to see to what extent the system is working effectively in realizing an up-to-date, accurate, and comprehensive voter list. The method used in this study is a descriptive qualitative approach. The collection of research data was obtained from a literature study of previous articles and using an interview technique with one of the employees at the Cianjur Regency KPU.